Analisis Makna Kanji Karui (軽い), Korobu (転ぶ), Yu (輸), Rin (論) yang Memiliki Bushu Kuruma - Felicia Felicia (Bina Nusantara University, 2012)
Article explored the difficulties of Japanese Learners’ beginners in learning kanji, especially those related to bushu kuruma, such as kanji 軽い、転ぶ、輸 and輪, Library Research was applied by compiling corpus data taken from Kanji Modern Jepang-Indonesia. The goal of the research was to observe whether kanji軽い、転ぶ、輸 dan輪 had any relation to bushu kuruma. It can be concluded that those four kanji has relation to bushu kuruma, even though kanji「輪」has no direct relation to bushu kuruma. From the four observed kanji, the three kanji「軽い」、「転ぶ」and「輪」are included in kanji keisei moji category, a kanji that represents meaning and vocal elements, while kanji「輸 includes in the kanji kai’I moji as a meaning combination between two or more pictographs or signs.